2020
DOI: 10.1039/c9cp06009j
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of C2 selectivity in electrochemical CO2reduction over oxide-derived copper

Abstract: Persistent Cu2O on ODCu plays an important role in C2 product selectivity due to its interactions with CO2RR intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Oxide Derived Copper: Neutral pHRecent studies have demonstrated that Cu materials derived from copper oxides (OD Cu) display high activity and selectivity for electroreduction of CO 2 to C 2 products (ethylene and ethanol) [45][46][47][48]. OD Cu electrodes are generally obtained by growing Cu 2 O layers from various Cu-based precursors (e.g.…”
mentioning
confidence: 99%
“…Oxide Derived Copper: Neutral pHRecent studies have demonstrated that Cu materials derived from copper oxides (OD Cu) display high activity and selectivity for electroreduction of CO 2 to C 2 products (ethylene and ethanol) [45][46][47][48]. OD Cu electrodes are generally obtained by growing Cu 2 O layers from various Cu-based precursors (e.g.…”
mentioning
confidence: 99%
“…One of the more interesting conclusions from the use of mixed oxides catalyst particles in the gas diffusion cathode was that ZnO and CuO, rather than metallic copper, control selective ethanol formation from carbon dioxide reduction 189. More recent works have concluded that the copper oxides at the surface are largely reduced during the carbon dioxide reduction reaction, but they also confirm that higher ethanol selectivity is obtained from cathode surfaces that initially had oxidized copper species present 64.…”
Section: Gas Phase/diffusion Cathodesmentioning
confidence: 72%
“…Whilst recent works still present evidence of the existence of Cu 2 O on the copper cathode surface during the reduction of carbon dioxide, there remains on‐going debate about the existence of sub‐surface unreduced ionic copper species that might promote this catalytic effect in the surface layers of copper, as most evidence indicates that the surface oxides are substantially, if not entirely, reduced 64, 65. It was concluded that both Cu 2 O and CuO were present prior to reduction and that the copper oxides were completely reduced to elemental copper during the carbon dioxide reduction reaction.…”
Section: Direct Electrochemical Reduction Of Carbon Dioxide To Ethylenementioning
confidence: 99%
“…Cu + of Cu x O catalysts prefers to adsorb intermediates, especially *CO, during the CRR process, and substantially convert CO 2 into ethylene. [ 69 ] Furthermore, some defect sites of Cu x O catalysts, such as oxygen vacancies, enhance the bond strength of *CO intermediate and ethylene selectivity. [ 75 ] Gu et al.…”
Section: Electrocatalystsmentioning
confidence: 99%